PENGARUH MARGIN DAN KUALITAS PELAYANAN ISLAMI TERHADAP KEUASAN ANGGOTA PADA PEMBIAYAAN MURABAHAH DI BMT MUAMALAT KALIBARU KABUPATEN BANYUWANGI - Khiliatul Jannah; Sofi Faiqotul Hikmah; Indana Almas Azhar (JPSDa: Jurnal Perbankan Syariah Darussalam, 2022)
This study aims to Knowing the Effect of Margin (X1) and Islamic Service Quality (X2) on Member Satisfaction (Y) on Murabahah Financing at BMT Muamalat Kalibaru. This study uses a quantitative approach to the type of explanatory research. The sample in this study was a member of BMT murabaha financing that had been a member of 1 year using probability sampling techniques obtained by the number of respondents 40 members. The analysis tool uses multiple linear regression with the help of SPPS 23. The results of the study 1) Margin (X1) has a positive and significant effect on Member Satisfaction (Y) on murabaha financing; 2) Islamic Service Quality has a positive and significant effect on Member Satisfaction (Y) on murabaha financing; 3) While from the simultaneous F test it is known that Margin (X1) and Islamic Service Quality (X2) have positive and significant effect on Member Satisfaction (Y) on murabaha financing at Muamalat Kalibaru BMT.